Design and implementation of a mobile system to provide personalised welfare information for people with disabilities: A pilot study - Suyeon Ban; Youngeun Kim; Yina Yoon; Ju Han Kim; Jisan Lee (Digital Health)
Background People with disabilities face challenges in accessing welfare information due to low digital literacy and non-user-friendly systems. This study aims to propose an initial framework for a mobile welfare information system that improves accessibility and welfare equity by focusing on personalised and user-friendly design tailored to specific needs of people with disabilities. Methods The study includes four stages. In Stage 1, key user needs for the system were identified. In Stage 2 South Korean and other countries’ welfare platforms were reviewed. In Stage 3, a back-end algorithm based on South Korea's national welfare platform, ‘Bokjiro’, was developed. In Stage 4, a core user interface (UI) was designed, focusing on perceived usefulness and ease of use. Results In Stages 1 and 2, we identified user needs, including personalised welfare information without service omissions, integration of welfare resources, regional comparisons and user-friendly features and found that these needs were not adequately addressed by existing platforms. In Stage 4, we designed a UI based on the identified needs. User interface features include comprehensive personalised information recommendations, driven by the algorithm developed in Stage 3 and regional welfare comparisons to enhance the perceived usefulness. To improve ease of use, scenario-based guidance and the level of disability-inclusiveness of welfare information were also incorporated. Conclusion This study proposes an initial framework for a mobile system that enhances access to welfare information for people with disabilities by addressing their needs. This approach would support people with disabilities in exercising their rights and improving their quality of life.